Contents and Distribution Pattern of Trace Elements in Groundwaters of Jodhpur District in Western Rajasthan - Gupta, S C; Sanganeria, M P; Rai, P C (Annals of Arid Zone, 2016)
Concentration and distribution pattern of some major trace elements viz., copper, iron, lead, lithium, manganese and zinc was studied in ground waters of Jodhpur district in western Rajasthan. The trace element concentrration varied considerably with respect to hydrogeology of the region, depth, salinily, total hardness and alkalinity. The average concentration of Cu, Fe, Pb,Li, Mn, andZn was found to be 31,516, 114,66,157 and 237!lgL-l with the maximum value of 125, 5610, 416,364, 1150 and 4000 !lg L-1 respectively.